Pharmacokinetics and Bioequivalence of Tiropramide in Healthy Volunteers - Kwon, Oh-Seung; Park, Young-Jin; Chung, Youn-Bok (Arzneimittelforschung, 2003)
Two formulations of tiropramlde ((±)α-(benzoylamino)-4- [2-(diethylamino) ethoxy]-N,N-dipropyl-benzenepropan-amide hydrochloride, CAS 55837-29-1), an antispasmodic agent, were orally administered to 16 healthy volunteers by the Latin cross-over design with the purpose of evaluating bioequivalence and pharmacokinetics of tiropramide. Tiropr-amide in human plasma was determined by a gas chromatography/nitrogen phosphorus detector. The detection limit of tiropramide was 5 ng/ml. Cmax values of test and reference formulations were 93.9 ± 54.3 and 96.4 ± 51.6 ng/ml, respectively. AUC0→last and AUC0→inf were 330.7 ± 193.9 and 349.5 ± 205.3 ng · h/ml, respectively, for the test formulation, 348.9 ± 207.7 and 380.8 ± 239.0 ng · h/ml, respectively, for the reference formulation. The terminal half-life was 2.34-2.61 h. Bioavailability differences for Cmax and AUC0→last were −2.48 % and −5.22 %, respectively. Minimum detection differences were less than 20 % for both Cmax and AUC0→last The 90 % confidence limits of geometric mean values for logarithmically transformed Cmax and AUCs were within 0.8-1.25. Based on these results, the two formulations of tiropramide are considered to be bioequivalent
Keywords: Antipsasmodic agent; CAS 55837-29-1; Tiromid®; Tiropramide, bioequivalence, clinical pharmacokinetics